Glial suppression and post-traumatic stress disorder: A cross-sectional study of 1,520 world trade center responders - Ginny Natale; Minos Kritikos; Pei-Fen Kuan; Melissa A. Carr; Xiaohua Yang; Yuan Yang; Roman Kotov; Evelyn J. Bromet; Sean A.P. Clouston; Benjamin J. Luft (Brain, Behavior, & Immunity - Health, 2023)
Background: Chronically re-experiencing the memory of a traumatic event might cause a glial response. This study examined whether glial activation would be associated with PTSD in a study of responders present after the 9/11 World Trade Center attacks without comorbid cerebrovascular disease. Methods: Plasma was retrieved from 1,520 WTC responders and stored for a cross-sectional sample of responders of varying levels of exposure and PTSD. Plasma levels (pg/ml) of glial fibrillary acidic protein (GFAP) were assayed. Because stroke and other cerebrovascular diseases cause distributional shifts in GFAP levels, multivariable-adjusted finite mixture models analyzed GFAP distributions in responders with and without possible cerebrovascular disease. Results: Responders were aged 56.3 years and primarily male; 11.07% (n = 154) had chronic PTSD. Older age was associated with increased GFAP, whereas higher body mass was associated with decreased GFAP. Multivariable-adjusted finite mixture models revealed that severe re-experiencing trauma from 9/11 was associated with lower GFAP (B = −0.558, p = 0.003). Conclusion: This study presents evidence of reduced plasma GFAP levels among WTC responders with PTSD. Results suggest re-experiencing traumatic events might cause glial suppression.